The transcriptomic and epigenetic alterations in type 2 diabetes mellitus patients of Chinese Tibetan and Han populations - Wang, Xian; Liu, Jie; Wang, Qiuhong; Chen, Qiu (Frontiers in Endocrinology, 2023)
Background: Due to the distinctive living environment, lifestyle, and diet, the Tibetan community in China has the lowest prevalence of T2DM and prediabetes among numerous ethnic groups, while Han community shows the highest statistic. In this study, we aim to conclude the clinical manifestations of both Tibetan and Han T2DM patients and their association with transcriptomic and epigenetic alterations. Methods: A cross-sectional study including 120 T2DM patients from Han and Tibetan ethnic groups were conducted between 2019 to 2021 at the Hospital of Chengdu University of Traditional Chinese Medicine. The various clinical features and laboratory tests were recorded and analyzed between the two groups. The genome-wide methylation pattern and RNA expression were determined by Reduced Representation Bisulfite Sequencing (RBBS) and Poly (A) RNA sequencing (RNA-seq) from leucocytes of peripheral blood samples in 6 Han and 6 Tibetan patients. GO analysis and KEGG analysis were conducted in differentially expressed genes and those with differentially methylated regions. Results: We identified 5178 hypomethylated and 4787 hypermethylated regions involving 1613 genes in the Tibetan group. RNA-seq showed a total of 948 differentially expressed genes (DEGs) between the two groups, with 523 up-regulated and 424 down-regulated in Tibetan patients. Functional enrichment analysis demonstrated that DEGs are mainly related to diPI3K-Akt, cAMP, Wnt, and Hippo signaling pathways. Functional enrichment analysis demonstrated that DEGs are mainly related to pancreatic secretion, fat digestion and absorption, metabolic pathways, IgA production, chemokine signaling pathway and cytokine-cytokine receptor interaction. By integrating DNA methylation and RNA expression data, we identified 112 DEGs with differentially methylated regions (DMRs) and 14 DEGs with promoter-related DMRs.